Identitas nasional dan budaya lokal: Upaya melestarikan jati diri bangsa - Azka, Muhammad Araffa (Maliki Interdisciplinary Journal, 2025)
A B S T R A C T This study aims to determine that national identity and local culture are important foundations in shaping the identity of a nation. In the midst of people being busy developing technology, foreign cultures are increasingly easy to enter and influence the mindset and lifestyle of Indonesian society, especially the younger generation. This condition can threaten the sustainability of local culture which is the heritage of our ancestors. This article discusses how important it is for us to maintain national identity and preserve local culture as an effort to strengthen the sense of love for the homeland and maintain the uniqueness of the Indonesian nation. Through education, involvement of the younger generation, and support from the community and government.